Effect of different alkaline solutions in cocoa powder alkalization: Effects on pasteurized chocolate milk - İlyas Atalar; Ayşe Apaydın; Ceren Elmacı; Tahra ElObeid; Nevzat Konar (Applied Food Research)
Alkalization results in significant changes in the characteristic properties of cocoa products. Different alkalized cocoa powders with varying properties are obtained depending on the alkaline solution used. However, no study has focused on how the properties of chocolate milk are influenced by the type of alkaline solution used. In this study, pasteurized chocolate milk samples containing alkalized cocoa powders, which were prepared through alkalization using different alkalis (NaOH, KOH, and K2CO3) at levels of 0.50, 1.00, and 1.50 g/100 mL, were prepared. The physicochemical properties (pH, dry matter content), sensory and color characteristics, flow behavior (viscosity, consistency index, flow index), total phenolic content (TPC), antioxidant capacities, and volatile compound profiles of the samples were examined. Additionally, during 30 days of storage at 4.00 °C, the color change (∆E) and zero-order rate constant (ko) for pH values were determined. Chocolate milk produced with KOH was found to have higher viscosity and consistency (p < 0.05). Using NaOH led to better color stability and higher levels of volatile compounds associated with chocolate and cocoa aromas. However, using K2CO3 for alkalization was advantageous in terms of TPC, antioxidant capacity, and more stable pH values during storage. It was determined that, especially for chocolate milk containing 1.00 and 1.50 g/100 mL of alkalized cocoa powder, using different alkaline solutions is necessary to increase the preference level for various sensory parameters. The study concluded that selecting an alkaline solution in the alkalization process of cocoa powder should be made based on the target consumer groups for chocolate milk and their consumption motivations.